Contribution of agricultural land uses to bird conservation: a case study of ecosystem service provisioning - Martinez Salinas, María A. (2016)
Tesis (Ph. D) - CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho (Estados Unidos), 2016